1995
DOI: 10.1074/jbc.270.40.23790
|View full text |Cite
|
Sign up to set email alerts
|

The Function of the NC1 Domains in Type IV Collagen

Abstract: At its C terminus, the collagen IV molecule bears a globular NC1 domain, to which two functions have been assigned. In the macromolecular network of collagen IV, two molecules are connected via their NC1 domains, which form a hexameric complex, stabilized by intermolecular disulfide bonds. In addition, the NC1 domains are thought to be responsible for chain selection and assembly. In order to understand the role of the NC1 domains during these steps, hexameric complexes were isolated and further investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…We have previously shown that ␣1(IV) and ␣2(IV) NC1 monomers from LBM hexamer can reassemble into NC1 hexamers in vitro, suggesting that the NC1 domains have a recognition function for the formation of triple-helical type IV collagen molecules and their assembly into networks (23). In contrast, a study of ␣1(IV) and ␣2(IV) NC1 domains from bovine placement basement membrane (39) reported that NC1 monomers interacted only weakly and that NC1 dimers were required for hexamer assembly. The reason for this disparity is unclear.…”
Section: Discussionmentioning
confidence: 98%
“…We have previously shown that ␣1(IV) and ␣2(IV) NC1 monomers from LBM hexamer can reassemble into NC1 hexamers in vitro, suggesting that the NC1 domains have a recognition function for the formation of triple-helical type IV collagen molecules and their assembly into networks (23). In contrast, a study of ␣1(IV) and ␣2(IV) NC1 domains from bovine placement basement membrane (39) reported that NC1 monomers interacted only weakly and that NC1 dimers were required for hexamer assembly. The reason for this disparity is unclear.…”
Section: Discussionmentioning
confidence: 98%
“…Polyclonal and monoclonal (M3F7) type IV collagen antibodies were from Southern Biotechnology Associates, Inc. and the Developmental Studies Hybridoma Bank (University of Iowa), respectively. Goat anti-mouse 5-nm colloidal gold conjugate was from Amersham Corp. Polyclonal antibodies against ␣1(IV) NC1 and ␣2(IV) NC1 were gifts from Klaus Kü hn (Martinsried, Munich) (19). The type VI collagen monoclonal antibodies N3-VI-2, C1-VI-1, and C12-VI-2 have been described previously (7).…”
Section: Methodsmentioning
confidence: 99%
“…The NC1 domain is thought to play a key role in the alignment and selection of three ␣ chains forming a triple helical molecule (10,11). Several studies have focused on the biological activity of the NC1 domain of type IV collagen.…”
mentioning
confidence: 99%